2021
DOI: 10.1111/1365-2435.13861
|View full text |Cite
|
Sign up to set email alerts
|

How to cope with drought and not die trying: Drought acclimation across tree species with contrasting niche breadth

Abstract: 1. Worldwide drought events have been reported to cause tree growth decline and mortality, thus altering the carbon (C) balance of forest ecosystems. While most of the attention has been focused on the physiological mechanisms associated with drought-induced tree responses of a few species at specific locations, the ecological attributes of these species, like their niche breadth, may be also important in determining species' sensitivity or resilience to drought. We postulated that wideniche breadth tree speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
0
9
2
Order By: Relevance
“…Nonetheless, in this study, at the intraspecific level, we found no support for this explanation. Furthermore, we did not find that high WD was associated with high concentrations of soluble sugars, although it has been suggested that they are capable of dealing with osmotic-demanding processes like drought-induced cavitation; for example, across several tree species, starch concentration has shown decreases and soluble sugar concentration increases under slight-tomoderate drought (Fajardo & Piper, 2021;He et al, 2020). Soluble sugars have also been hypothesised to maintain their vascular integrity in dry climates (Brodersen & McElrone, 2013;Sala et al, 2012); in addition, they have been shown to be important for post-drought recovery in saplings and adult trees of Fitzroya cupressoides (Urrutia-Jalabert et al, 2020) in temperate forests, as well as in several Mediterranean species (Lloret et al, 2018).…”
Section: Wood Density and C Reservescontrasting
confidence: 80%
See 2 more Smart Citations
“…Nonetheless, in this study, at the intraspecific level, we found no support for this explanation. Furthermore, we did not find that high WD was associated with high concentrations of soluble sugars, although it has been suggested that they are capable of dealing with osmotic-demanding processes like drought-induced cavitation; for example, across several tree species, starch concentration has shown decreases and soluble sugar concentration increases under slight-tomoderate drought (Fajardo & Piper, 2021;He et al, 2020). Soluble sugars have also been hypothesised to maintain their vascular integrity in dry climates (Brodersen & McElrone, 2013;Sala et al, 2012); in addition, they have been shown to be important for post-drought recovery in saplings and adult trees of Fitzroya cupressoides (Urrutia-Jalabert et al, 2020) in temperate forests, as well as in several Mediterranean species (Lloret et al, 2018).…”
Section: Wood Density and C Reservescontrasting
confidence: 80%
“…Most of wood anatomy, leaf and chemical traits changed across gradients as well (Table 2; Table S2). These particular trait-gradient results were reported and discussed in previous studies (Fajardo & Piper, 2021;García-Cervigón et al, 2018;García-Cervigón et al, 2020) and they will not be covered in this study unless they help to explain WD-other traits relationships.…”
Section: General Trends Of Wd and Traits Variation Across Speciesmentioning
confidence: 88%
See 1 more Smart Citation
“…Forest ecosystems are constantly facing changing environmental and climatic conditions, but it is becoming obvious that they are becoming greatly affected by more frequent and prolonged droughts [1][2][3]. Over the coming decades, climate change will accelerate tree dieback due to severe drought and heat stress in many areas [4][5][6][7], especially in semiarid regions where significant decreases in forest productivity and growth stability are expected [8][9][10][11][12]. The sensitivity of trees to drought should be assessed within ecological gradients (natural zones), since the expected climate change effects depend much on the local habitat conditions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The response of trees to climatic variables can be significantly modified by topography and soil features, species characteristics, and even individual genetic factors [18][19][20][21][22]. Clearly, species-specific modulation of climate response may be associated with their physiological strategies of coping with stress [23,24], although abiotic factors acting at the community level may cause similar responses [7]. The resilience of forest growth to extreme events, including droughts, also depends not only on the intensity and duration of stress, but also on the forest stand structure [25,26].…”
Section: Introductionmentioning
confidence: 99%